2015
DOI: 10.1038/eye.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pigment epithelium transplantation: concepts, challenges, and future prospects

Abstract: The retinal pigment epithelium (RPE) is a single layer of cells that supports the light-sensitive photoreceptor cells that are essential for retinal function. Age-related macular degeneration (AMD) is a leading cause of visual impairment, and the primary pathogenic mechanism is thought to arise in the RPE layer. RPE cell structure and function are well understood, the cells are readily sustainable in laboratory culture and, unlike other cell types within the retina, RPE cells do not require synaptic connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 74 publications
0
44
0
3
Order By: Relevance
“…3,4 Thus, a dysfunction of the RPE can lead to retinal diseases such as agerelated macular degeneration (AMD) and photoreceptor degeneration. 5,6 AMD is a degenerative retinal-choroidal disease and the leading cause of blindness in the elderly in developed countries. 7 Exudative AMD is characterized by choroidal neovascularizations, and nonexudative AMD is characterized by geographic atrophy of the RPE.…”
mentioning
confidence: 99%
“…3,4 Thus, a dysfunction of the RPE can lead to retinal diseases such as agerelated macular degeneration (AMD) and photoreceptor degeneration. 5,6 AMD is a degenerative retinal-choroidal disease and the leading cause of blindness in the elderly in developed countries. 7 Exudative AMD is characterized by choroidal neovascularizations, and nonexudative AMD is characterized by geographic atrophy of the RPE.…”
mentioning
confidence: 99%
“…Intra-und postoperative Komplikationen zehren die mögliche Sehverbesserung auf. Trotzdem hält das wissenschaftliche Interesse an den Transplantationsverfahren an [8]. Bis heute gibt es für 90 % der AMD-Patienten, diejenigen mit der trockenen Verlaufsform, keine Behandlungsoption.…”
Section: Zelltransplantation Zur Behandlung Der Altersabhängigen Makuunclassified
“…Numerous studies have showed encouraging results by transplanting RPE suspensions or RPE sheets into the subretinal space of animal models [4][5][6][7]. However, AMD patients who received RPE transplantation did not achieve significant visual improvements in FDAapproved clinical trials [8,9].…”
Section: Introductionmentioning
confidence: 97%